UPAYA MENINGKATKAN AKTIVITAS BELAJAR IPA DENGAN MODEL PEMBELAJARAN ACTIVE LEARNING TIPE PEER LESSON PADA SISWA KELAS V SDN 017 RANAH SINGKUANG - Resnalti Resnalti; Sumianto Sumianto; Melvi Lesmana Alim; Rizki Ananda; Joni Joni (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
This research was motivated by the low learning activity of fifth-grade students of UPT SD Negeri 017 Singkuang Ranch. This study aims to increase the learning activities of fifth-grade students of UPT SD Negeri 017 Singkuang Ranah, which consists of 25 students. The research used was Classroom Action Research (PTK), carried out in two learning cycles. Each cycle consists of two meetings and four learning stages: planning, implementing, observing, and reflecting. Data collection techniques in the form of documentation, observation, and tests. In contrast, the data analysis technique uses qualitative analysis and quantitative analysis. Based on the data analysis, the results of the learning activities of class V UPT SD Negeri 017 Ranah Singkuang in the pre-action were obtained with a learning completeness percentage of 63.04%. In Cycle 1 Meeting I, with a learning completeness percentage of 67.61%, and in Cycle 1 Meeting II, there was an increase with a learning completeness percentage of 72%. In cycle two, the first meeting also increased with the rate of learning activities at 75.62%. In cycle 2, the second meeting experienced another increase, with the speed of learning completeness at 84.75%. Thus, applying the peer lesson type active learning model can increase the learning activities of class V UPT SD Negeri 017 Ranah Singkuang.Keywords : Model Active learning type peer lesson, Activities learning and Elementary School Students